L-proline as Co-crystal Forming Amino Acid for Enhanced Dissolution Rate of Lamotrigine: Development of Buccal Tablet - Abdelrahman, Howaida; Essa, Ebtesam; El Maghraby, Gamal; Arafa, Mona (Indonesian Journal of Pharmacy, 2023)
Lamotrigine is an antiepileptic drug with slow dissolution rate which can reduce its oral bioavailability. In addition, it was reported to have first pass metabolism. Accordingly, the aim of this work was to enhance its dissolution rate utilizing co-crystallization technique to be suitable for incorporation in buccal dosage form. L-proline was selected as co-crystal co-former for enhancing dissolution in addition to its beneficial anticonvulsant properties. Formulations containing lamotrigine and L-proline at different molar ratios were prepared using ethanol assisted co-grinding. The prepared formulations were characterized using FTIR, X-Ray powder diffraction, differential scanning calorimetry and dissolution studies. The formulation recorded the highest dissolution rate was incorporated in fast disintegrating tablet for buccal use. Characterization techniques suggested the formation of lamotrigine-l-proline co-crystals with 1:2 molar ratio being optimum for interaction. This interaction resulted in significant enhancement in dissolution rate with the ratio of lamotrigine to proline at molar ratio of 1:4 showed greatest dissolution rate (% DE= 80.57). The prepared tablet utilizing lamotrigine and L-proline at molar ratio of 1:4 showed fast disintegration and rapid dissolution rate compared with control tablet containing lamotrigine alone. The study suggested L-proline as an efficient co-crystal co-former for enhancing dissolution rate of lamotrigine for buccal delivery.